2016
DOI: 10.1159/000449376
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Serious Drug-Drug Interactions in Older Patients Hospitalized for Acute Ischemic and Hemorrhagic Stroke

Abstract: Background: Polypharmacy is very common in older persons and it is associated with inappropriate prescribing and potential drug-drug interactions (DDIs). Aims of this study were to identify prevalence of DDIs in older persons with acute stroke and to evaluate the association between stroke and DDIs. Methods: One hundred forty-six patients admitted with diagnosis of acute stroke were enrolled. The therapeutic regimen of patients was analyzed at admission to identify the number of DDIs, prevalence and sorts of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
1
18
2
Order By: Relevance
“…Furthermore, in current study, prevalence of major-pDDIs is higher (19.3%) as compared to that reported among patients with cancer (16%) [16]. Whereas, it is lower in comparison to that reported among patients with liver cirrhosis (21.4%) [12], hepatitis C (30-44%) [20], and stroke (61%) [17]. Similarly, the prevalence of contraindicated-pDDIs in patients with malaria is also lower (14.3%) in comparison to the prevalence reported among patients with hepatitis C (16.7%) [30].…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, in current study, prevalence of major-pDDIs is higher (19.3%) as compared to that reported among patients with cancer (16%) [16]. Whereas, it is lower in comparison to that reported among patients with liver cirrhosis (21.4%) [12], hepatitis C (30-44%) [20], and stroke (61%) [17]. Similarly, the prevalence of contraindicated-pDDIs in patients with malaria is also lower (14.3%) in comparison to the prevalence reported among patients with hepatitis C (16.7%) [30].…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore in current study, prevalence of major-pDDIs is higher (19.3%) as compared to that reported among patients with cancer (16%) [15]. Whereas, it is lower in comparison to that reported among patients with liver cirrhosis (21.4%) [11], hepatitis C (30-44%) [19], and stroke (61%) [16]. Similarly, the prevalence of contraindicated-pDDIs in patients with malaria is also lower (14.3%) in comparison to the prevalence reported among patients with hepatitis C (16.7%) [25].…”
Section: Discussioncontrasting
confidence: 65%
“…Potential DDIs (pDDIs) issue has been addressed generally in hospitalized patients [7] as well as in specific diseases such as liver cirrhosis [11], hypertension [12], diabetes mellitus (DM) [13], bone marrow transplant [14], cancer [15], stroke [16], pneumonia [17], urinary tract infections [18], and hepatitis C [19]. Despite, being the most prevalent causes of hospitalization [20], DDIs particularly among inpatients with malaria remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern because the sensitivity to side effects of drugs also increases with age, as a result of decreased renal function, cognitive function and body composition [2]. In addition, polypharmacy increases the risk of adverse drug events (ADEs), drug–drug interactions and medication errors in the elderly [3, 4]. Previous studies have shown that drug-related problems (DRPs) are common.…”
Section: Introductionmentioning
confidence: 99%